A Fuzzy Multi-criteria Decision Making Model for the Selection of the Distribution Center - Lee, Hsuan-Shih (Advances in Natural Computation, 2005)
The location selection of distribution is one of the most important decision issues for logistic managers. In order to encompass vagueness in decision data, a new fuzzy multiple criteria decision-making method is proposed to solve the distribution center selection problem under fuzzy environment. In the proposed method, the ratings of alternatives and the weights of the criteria are given in terms of linguistic variables which is in turns represented by triangular fuzzy numbers.